Peptide specific monoclonal antibodies of Leptospiral LigA for acute diagnosis of leptospirosis - Murugesan Kanagavel (Nature Portfolio, 2017)
Abstract Leptospirosis is underdiagnosed due to low sensitivity, need of specialised equipment, and expensive reagents for serological and molecular diagnosis respectively. Considering the sensitivity, rapidity, inexpensive reagents and collection of clinical samples, the monoclonal antibody based antigen detection method from urine samples has been developed and evaluated. LigA (LK90) based B-cell specific epitopes were predicted and synthesised as peptides for the production of monoclonal antibody. LK90543: SNAQKNQGNA (amino acids: 543 to 552), and LK901110: DHHTQSSYTP (amino acids: 1110 to 1119) with VaxiJen score of 1.3719 and 1.2215, respectively were used. Thirty two and 28 urine samples from confirmed and seronegative healthy human subjects, respectively were included for the evaluation of MAb-based dot blot ELISA. The specificity of the evaluated MAbs, P1B1 and P4W2 were found to be in the range of ~93–96%. Moreover, the MAbs did not show cross-reactivity with other bacterial antigens as confirmed by IgG ELISA, further validating its specificity for leptospiral antigens. These findings suggest that the developed MAb based dot blot ELISA is a simple, rapid performed in less than 8 h, inexpensive with a ICER of $8.7/QALY, and affordable in developing countries and area where laboratory facilities are limited.